Mid‐childhood outcomes of infant siblings at familial high‐risk of autism spectrum disorder. Issue 3 (29th November 2016) - Shephard, Elizabeth; Milosavljevic, Bosiljka; Pasco, Greg; Jones, Emily J. H.; Gliga, Teodora; Happé, Francesca; Johnson, Mark H.; Charman, Tony; ,
Abstract : Almost 20% of infants with an older sibling with autism spectrum disorder (ASD) exhibit ASD themselves by age 3 years. The longer‐term outcomes of high‐risk infants are less clear. We examined symptoms of ASD, attention‐deficit/hyperactivity disorder (ADHD) and anxiety, language, IQ, and adaptive behaviour at age 7 years in high‐ and low‐risk children prospectively studied since the first year of life. Clinical outcomes were compared between high‐risk children who met diagnostic criteria for ASD at age 7 (HR‐ASD‐7 group, n = 15), high‐risk children without ASD (HR‐Non‐ASD‐7 group, n = 24), and low‐risk control children (LR group, n = 37). Diagnostic stability between age 3 and 7 years was moderate, with five children who did not meet diagnostic criteria for ASD at age 3 years being assigned the diagnosis at age 7, and three children showing the opposite pattern. The HR‐ASD‐7 group showed elevated ADHD and anxiety symptoms and had lower adaptive behaviour scores than LR controls. The HR‐Non‐ASD‐7 group had higher repetitive behaviour, lower adaptive functioning and elevated scores on one anxiety subscale (Separation Anxiety) compared to LR controls, but evidence for subclinical ASD symptoms (the broader autism phenotype, BAP) was limited in the group as a whole, although we identified a subgroup with elevated ASD traits. The difficulties experienced by high‐risk siblings at school‐age extend beyond ASD symptoms. The pattern of difficulties exhibited by the HR‐ASD‐7 group may inform our understanding of developmental trajectories of co‐occurring psychopathology in ASD. Autism Res 2017, 10: 546–557 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.